Studi Kelayakan Penggunaan Material Lokal Berupa Agregat Kasar dan Agregat Halus di Kabupaten Jayapura Sebagai Bahan Dasar Stone Matrix Asphalt (SMA) Kasar - Muhammad Arie Nugraha; Bahtiar Bahtiar; Davy I.R. Jansen (Jurnal Sipil Terapan, 2024)
Flexible pavement is the most widely used pavement in Indonesia. There are three types of hot mix asphalt in Spesifikasi Umum Bina Marga 2018 Rev. 2, including Asphalt Concrete (AC), Thin Layer Asphalt Concrete (Hot Rolled Sheet, HRS) and Stone Matrix Asphalt (SMA). Of the three types of hot mix asphalt Stone Matrix Asphalt has advantages but is rarely used in Indonesia, especially in Papua. This is what then motivated the author to raise the research topic to find out whether local materials in the Jayapura Regency area can be utilized as a basic material for Rough Stone Matrix Asphalt (SMA).This research was conducted at the BPJN Jayapura Testing Laboratory with asphalt levels of 5.5%, 6.0%, 6.5%, 7.0% and 7.5%. Coarse aggregate in the form of crushed stone and stone ash was obtained from Kampung Harapan, Jayapura Regency while sand was obtained from River at Waibu District Jayapura Regency and filler from stone ash. The results of the water absorption test stated that the aggregate from Kampung Harapan had a value greater than 2% and sand 0.872%. The marshall test results showed that the stability and flow values continued to increase with the addition of asphalt content and decreased at 7.5% asphalt content. While the Void In Mix value decreased with the addition of asphalt content and the Void In Mineral Aggregate value continued to increase with the addition of asphalt content although it was still below the standard. Optimum Asphalt Content is obtained with a value of 6.13%. The residual strength index is 84.77%. As for the price difference between Stone Matrix Asphalt Rough is more expensive by 15.02% compared to the Intermediate Layer Laston (AC - BC).